Validation of wing geometric morphometrics in Chrysodeixis spp. (Lepidoptera: Noctuidae) to support pest identification in invasive species survey programs - Smith-Pardo, Allan H.; Torres, Karina M.; Paula-Moraes, Silvana V. (Frontiers in Insect Science, 2025)
Looper moths of the genus Chrysodeixis (Lepidoptera: Noctuidae: Plusiinae) are important pests of many crops and native plants worldwide. Chrysodeixis chalcites (Esper) is listed as an invasive species for the United States with records of interception. Native species of the Plusiinae subfamily are morphologically similar and commonly cross-attracted in survey trapping programs for C. chalcites, such as Chrysodeixis includens (Walker), a native economic pest. The species identification relies on male genitalia dissection and DNA analysis. These processes are time and cost-consuming and require expertise. In this work, we evaluated the use of wing geometric morphometrics (GM) as a tool to overcome the identification challenges associated with the complex morphologies of Chrysodeixis spp. The cleaned wings of specimens with validated identification were photographed under a digital microscope, and seven venation landmarks were annotated from the images. The digital coordinates of the wing landmarks were analyzed in MorphoJ. Our results validated the use of GM for distinguishing the invasive C. chalcites from the native C. includens. A limited number of landmarks on the center of the wing was used to address the challenges in GM for trap-collected lepidopteran pests. Future automation of the novel application of GM for identifying C. includens can be explored in trapping systems for IPM and surveys for the invasive C. chalcites.